Acute-on-Chronic Liver Failure in China: Rationale for Developing a Patient Registry and Baseline Characteristics. Issue 9 (14th May 2018) - Gu, Wen-yi; Xu, Bao-yan; Zheng, Xin; Chen, Jinjun; Wang, Xian-bo; Huang, Yan; Gao, Yan-hang; Meng, Zhong-ji; Qian, Zhi-ping; Liu, Feng; Lu, Xiao-bo; Shang, Jia; et al.
Abstract: Definitions and descriptions of acute-on-chronic liver failure (ACLF) vary between Western and Eastern types, and alcoholism and hepatitis B virus (HBV) are, respectively, the main etiologies. To determine whether there are unified diagnostic criteria and common treatment programs for different etiologies of ACLF, a multicenter prospective cohort with the same inclusion criteria and disease indicators as those used in the European Consortium Acute-on-Chronic Liver Failure in Cirrhosis Study is urgently needed in Asia, where the prevalence of HBV is high. A multicenter prospective cohort of 2, 600 patients was designed, drawing from 14 nationwide liver centers from tertiary university hospitals in China, and 2, 600 hospitalized patients with chronic liver disease (both cirrhotic and noncirrhotic) of various etiologies with acute decompensation or acute hepatic injury were continuously recruited from January 2015 to December 2016. Data were collected during hospitalization, and follow-ups were performed once a month, with plans to follow all patients until 36 months after hospital discharge. Of these patients, 1, 859 (71.5%) had HBV-related disease, 1, 833 had cirrhotic disease, and 767 had noncirrhotic disease. The numbers and proportions of enrolled patients from each participating center and the baseline characteristics of the patients with or without cirrhosis are presented.